2016
DOI: 10.1021/acs.jmedchem.6b00108
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin II(4–11) Azasulfuryl Peptides: Synthesis and Biological Activity

Abstract: Cyclic azasulfuryl (As) peptide analogs of the urotensin II (UII, 1, H-Glu-Thr-Pro-Asp-c[Cys-Phe-Trp-Lys-Tyr-Cys]-Val-OH) fragment 4-11 were synthesized to explore the influences of backbone structure on biological activity. N-Aminosulfamides were inserted as surrogates of the Trp(7) and Lys(8) residues in the biologically relevant Trp-Lys-Tyr triad. A combination of solution- and solid-phase methods were used to prepare novel UII((4-11)) analogs 6-11 by routes featuring alkylation of azasulfuryl-glycine tripe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…20,21 In particular, the resins were washed with DCM (2 mL × 3), suspended in a solution of Pd(PPh 3 ) 4 (0.15 equiv) and N , N ′-dimethylbarbituric acid (NDMBA) (7 equiv) in 3:2 dry DCM/DMF (v/v), and placed in a 20 mL μ W reaction vessel. The vessel was sealed and heated to 40 °C using μ W irradiation for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…20,21 In particular, the resins were washed with DCM (2 mL × 3), suspended in a solution of Pd(PPh 3 ) 4 (0.15 equiv) and N , N ′-dimethylbarbituric acid (NDMBA) (7 equiv) in 3:2 dry DCM/DMF (v/v), and placed in a 20 mL μ W reaction vessel. The vessel was sealed and heated to 40 °C using μ W irradiation for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past few years, our search for new modulators led to the discovery of an azasulfuryl urotensin II derivative, i.e. [AsNal(2') 7 ]UII (4–11) (Figure ), that can exert a probe‐dependent action on UII and URP biological activity . Altogether, modification/substitution of the Trp residue in UII and URP represent a new avenue toward the conception of UT ligands with unique pharmacological profile.…”
Section: Development Of the First Ut Allosteric Modulators Through Trmentioning
confidence: 99%
“…So far, none of the UT antagonists has been investigated for their ability to also block URP‐mediated function. However, recently developed peptidic and non‐peptidic UT antagonists have demonstrated a wide range of activity against UII‐ and URP‐mediated function . For instance, R‐4a (Figure ) inhibited completely hUII‐induced contractions but increased tremendously URP‐associated vasoconstriction .…”
Section: Nonpeptidic Antagonists With Probe‐dependent Functionsmentioning
confidence: 99%
“…Urotensin‐II (U‐II) is a kind of growth hormone‐like neuropeptide, which is ubiquitous in many tissues and organs of mammals, including humans . A large number of studies have shown that the combination of human U‐II (hUII) and its receptor (urotensin receptor, UTR) can produce various biological effects and play an important role in the occurrence and the development of various cardiovascular diseases . RhoA is one of the effectors of the small GTP‐binding protein.…”
Section: Introductionmentioning
confidence: 99%
“…[5] A large number of studies have shown that the combination of human U-II (hUII) and its receptor (urotensin receptor, UTR) can produce various biological effects and play an important role in the occurrence and the development of various cardiovascular diseases. [6,7] RhoA is one of the effectors of the small GTP-binding protein. RhoA and its downstream target molecules Rho-related coiled-coil-forming protein kinase (ROCK) participate in the regulation of a variety of physiological functions and various pathological processes.…”
Section: Introductionmentioning
confidence: 99%